The impact of trade conflict on developing Asia - Abdul Abiad; Kristina Baris; John Arvin Bernabe; Donald Jay Bertulfo; Shiela Camingue-Romance; Paul Neilmer Feliciano; Mahinthan Joseph Mariasingham; Valerie Mercer-Blackman (Asian Development Bank (ADB), 2018)
This paper analyzes the effects of the current trade conflict on developing Asia using the Asian Development Bank's Multiregional Input - Output Table (MRIOT), allowing us to calculate the impact on individual countries and on sectors within countries. The analysis estimates the direct impact on all tariff-affected goods; uses input-output analysis to estimate indirect effects on gross domestic product (GDP), exports, and employment; and allows for redirection of trade toward other producers using the approach of Feenstra and Sasahara (2017). A full escalation of the bilateral United States (US) - People's Republic of China (PRC) trade conflict would shave 1% off PRC GDP and 0.2% off US GDP. The rest of developing Asia could see small net gains thanks to trade redirection, particularly in the electronics sector. A trade war in autos and parts would hurt the European Union and Japan. The conflict has substantial negative effects on PRC and US employment, but only minor impacts on current account balances.
Keywords: E00; F13; F14; O47; 330; exports; input-output; international trade; tariffs; trade conflict; trade redirection